2019
DOI: 10.1002/btpr.2935
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of factors influencing enzyme activity and product selectivity and the role of proton transfer in the catalytic mechanism of patchoulol synthase

Abstract: The patchoulol synthase (PTS) from Pogostemon cablin is a versatile sesquiterpene synthase and produces more than 20 valuable sesquiterpenes by conversion of the natural substrate farnesyl pyrophosphate (FPP). PTS has the potential to be used as a biocatalyst for the production of valuable sesquiterpenes such as (−)‐patchoulol. The objective of the present study is to develop an efficient biotransformation and to characterize the biocatalytic mechanism of the PTS in detail. For this purpose, soluble PTS was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“… 46 The in vivo optimal pH (found here) is similar to that of the in vitro biotransformation reactions, determined between pH 6.4–6.6. 42 Accordingly, our results are similar to the E. coli strains used for the production of longifolene 47 and sclareol, 48 which used a pH of 7.0 during cultivation. Thereafter, the cultivation conditions of 20 °C and pH 6.75 were used for further evaluations.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“… 46 The in vivo optimal pH (found here) is similar to that of the in vitro biotransformation reactions, determined between pH 6.4–6.6. 42 Accordingly, our results are similar to the E. coli strains used for the production of longifolene 47 and sclareol, 48 which used a pH of 7.0 during cultivation. Thereafter, the cultivation conditions of 20 °C and pH 6.75 were used for further evaluations.…”
Section: Resultssupporting
confidence: 79%
“…Nevertheless, the lowest temperature tests did not produce the highest (−)-patchoulol titers; possibly, due to the diminished enzyme activity of the (−)-patchoulol synthase. This could be supported because in previous in vitro biotransformation reactions, 42 (−)-patchoulol synthase showed higher activity at higher temperatures, reaching its maximum at 34 °C. Therefore, a balance is required among the production of soluble (−)-patchoulol synthase protein, enzyme activity, and cell growth, as observed in the tests grown at 20 °C, which achieved the highest (−)-patchoulol production.…”
Section: Resultssupporting
confidence: 56%
“…atoms was reported that is explainable by the deprotonation step from E to 6 [10], but contradicts the retainment of this hydrogen as reported by Croteau [9]. Further support for Akhila's mechanism was provided by Ekramzadeh et al, who observed the uptake of two deuterium atoms at C3 and C12 in an incubation of FPP with PTS in deuterium oxide buffer that explain the reprotonations of the neutral intermediates 8 and 6 (Scheme 2C) [13].…”
Section: Introductionmentioning
confidence: 92%
“…For both experiments a full retainment of labelling was reported for all intermediates until 13, while a loss of tritium was observed for 14 with both substrates. From these experiments it was concluded that the hydrogen H6 must migrate into another position, as realised by the 1,4-hydride shift from C to D. The loss of 3 H in the experiment with [12,[13][14] C,1-3 H]FPP was expected for the aldol reaction of 13, but is more difficult to understand in the experiment with [12,13-14 C,6-3 H]FPP. In this case the loss of 3 H was explained by an exchange against 1 H during catalytic hydrogenation [9].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation